Usefulness of the concept of social savings and consumer surplus in studies on the impact of innovation on economic growth - Janusz Krzysztof Myszczyszyn (The Central European Review of Economics and Management (CEREM), 2018)
Aim: The main objective of the paper was to calculate social savings (and consumer surplus) of innovation on the example of railroads in Germany for 1985. The railways were among the most important innovations in the nineteenth century. Being aware of the limits of the social savings technique, the author included the concept of consumer surplus in his calculation~Design / Research methods: For the purpose of the research, the author used the concept of social savings proposed by Robert Fogel and consumer surplus.~Conclusions / findings: For the year 1895, social savings amounted to 2.82% (first equation) of GDP and 5.04% of GDP (second equation), taking into account elasticity of demand (-1,38), social savings amounted to 1.27% of GDP and 2.18% of GDP for Germany. The result thus elicited the author referred to the social savings from railroads as made available in literature and the author's previous research. The author demonstrated that the social savings from the innovation were relatively small.~Originality / value of the article: The results of research are useful for examining the impact of innovation, such as railroads, on the level of social savings. The paper fills the gap in the Polish economic thinking on the use of counterfactual methods.~Implications of the research: The concept of social savings which takes into account demand elasticity can be applied successfully in evaluating the impact of (various) innovations on economic growth.~Limitations of the research: The weakness of the method may be the lack of knowledge about the real level of elasticity of demand for innovation, as well as determining the level of prices of an alternative good, especially if the use of innovation at the initial stage of bringing it to the market involves a relatively high price.
Keywords: N73; O30; R11; 330; Social savings; consumer surplus; elasticity of demand; innovation; rail transport